CCAFS CU Carbon footprint report 2015 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In 2011 CCAFS Coordinating Unit (CCAFS CU) initiated a carbon footprint plan including emission reduction targets and offsetting. This report follows up on actions and targets for 2015.